Some geotechnical properties of pure and waste gypsum for geoelectrical grounding applications - Mohd Tadza, Mohd Yuhyi; Mazelan, Nurmazuria; Yusri, Nur Farahana; Abdullah, Amizatulhani (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Natural occurring gypsum is a soft mineral consists of hydrated calcium sulphate, mainly used in cement industry. On the other hand, red gypsum (RG) is a waste generated from a sulphate process of ilmenite ore to acquire titanium dioxide. Due to the gypsum content in both materials are similar, it is expected that both gypsum type can be used for similar engineering applications.
Keywords: gypsum; waste gypsum; geotechnical properties; geoelectrical grounding applications; plasticity; gips; gips odpadowy; właściwości geotechniczne; uziemienie; plastyczność